Pengaruh Profitabilitas, Aktivitas Perusahaan, Likuiditas, Solvabilitas, dan Financial Distress terhadap Opini Audit Going Concern - Jannah, Richatul; Rizkyana, Fitrarena Widhi; Pertiwi, Meilani Intan; Tinambunan, Cecilia Ardani (Universitas Muhammadiyah Metro, 2025)
This research aims to test the influence of profitability, company activity, liquidity, solvency, and financial distress on going concern audit opinion. The population in this research is apparel & luxury goods subsector companies listed on the Indonesian Stock Exchange (IDX) in 2016-2023 with a total of 26 companies resulting in 13 companies with a total of 104 units of analysis. This research uses secondary data with documentation techniques. The analysis method uses the SPSS version 26 for statistical application. The analysis of this research show that profitability, company activity, and liquidity have a negative effect on going concern audit opinion. Conversely, solvency and financial distress have no effect on going concern audit opinion. Further research may consider adding other variables such as corporate governance and company size, analysis of other industrial sectors, or the use of more complex analysis methods to obtain more in-depth results and broader generalizations.